OPTIMIZATION OF CLAY MASK FORMULA FROM LEAF SI KEJUT (Mimosa pudica L.) EXRACT USING SIMPLEX LATTICE DESIGN METHOD - Fitriawati, Anna; Rahmatillah, Annie; Agustiningrum, Nurul (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Clay mask is a facial mask used to remove dirt and blackheads from the skin. It is particularly suitable for acne-prone skin, as clay masks provide a refreshing sensation, absorb excess oil, and help manage blackheads. Mimosa pudica, commonly known as the "Sensitive Plant" or "Touch-me-not," contains bioactive compounds such as alkaloids, flavonoids, tannins, and saponins. According to a study by Utami et al. (2021), Mimosa pudica L. leaves exhibit strong inhibitory effects against Propionibacterium acnes, the primary bacterium responsible for acne. The objective of this research is to determine the optimal formulation of ethanol extract from Mimosa pudica leaves in a clay mask using the Simplex Lattice Design (SLD) method. Optimization was performed by comparing two clay base formulations—kaolin and bentonite. Physical quality testing included organoleptic evaluation, homogeneity, adhesion strength, spreadability, pH testing, and drying time. The results of the physical quality tests were analyzed using Design Expert software. Through the Simplex Lattice Design (SLD) method, the optimal formula was identified as Formula I, containing 34.75% kaolin and 6.25% bentonite.